2009
DOI: 10.1007/s10725-009-9364-1
|View full text |Cite
|
Sign up to set email alerts
|

Allelochemical stress produced by aqueous leachate of Nicotiana plumbaginifolia Viv.

Abstract: The effects of aqueous leachate of Nicotiana plumbaginifolia Viv. on germination, seedling growth, amylase activity, sugar and starch contents of germinated seeds of maize (Zea mays L. cv. Uttam) were examined. Effects of leachate on photosynthetic pigments, protein content, activities of nitrate reductase and some antioxidants were also studied. Higher concentration of aqueous leachate of N. plumbaginifolia reduced the germination rate (GR). However, final germination percentage remained almost unaffected. Lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 41 publications
2
36
0
3
Order By: Relevance
“…The phytotoxicity of phenolic compounds seems to be due to the disruption and inhibition of certain processes during the germination stage. They cause inhibition of seed germination not only by induction of oxidative stress but also by restriction on reserve mobilization; it is because phenolics can inhibit the activities of α-amylase and gibberellic acid (Politycka and Gmerek, 2008;Singh et al, 2009;Das et al, 2012). Golisz et al (2008) noted that some alellochemicals can cause root cell death indirectly by facilitating the production of ROS, which may also act as signaling molecules leading to changes in hormonal balance during the seed germination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phytotoxicity of phenolic compounds seems to be due to the disruption and inhibition of certain processes during the germination stage. They cause inhibition of seed germination not only by induction of oxidative stress but also by restriction on reserve mobilization; it is because phenolics can inhibit the activities of α-amylase and gibberellic acid (Politycka and Gmerek, 2008;Singh et al, 2009;Das et al, 2012). Golisz et al (2008) noted that some alellochemicals can cause root cell death indirectly by facilitating the production of ROS, which may also act as signaling molecules leading to changes in hormonal balance during the seed germination.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that phenolics are able to inhibit plant cell division, root elongation, change cell ultrastructure, and interfere with the normal growth and development of the whole plant (Li et al, 2010). Singh et al (2009) reported that the reduced chlorophyll under leachate treatments could be attributed to the inhibition of chlorophyll biosynthesis and/or the stimulation of chlorophyll degradation. Cell ultrastructure Fig.…”
Section: Discussionmentioning
confidence: 99%
“…According to Singh et al (2009), phytotoxins can aff ect enzyme activities or plant hormones, increasing amylase activity and promoting a greater release of reserves that would otherwise be provided to the embryo, extending oxidative stress and seed dormancy through the increase of abscisic acid production and inhibiting water absorption via alterations in membrane permeability. Th e same author also observed a reduction in protein content and nitrate reductase activity in corn root tissues exposed to Nicotiana plumbaginifolia leachates.…”
Section: Discussionmentioning
confidence: 99%
“…Th e growth of neighboring vegetation might be aff ected and a selective advantage thus aff orded the donor plant (Anaya 1999). Allelochemicals aff ect various metabolic processes in or-ganisms: altering membrane permeability and ion absorption ; inhibiting electron transport in photosynthesis and respiration (Abrahim et al 2000); changing enzyme activity (Singh et al 2009); and impeding cell division (Teerarak et al 2010). Because of these eff ects, allelopathy is recognized as an important ecophysiological process in ecosystems, infl uencing primary and secondary plant succession, as well as the structure, composition and dynamics of native or cultivated plant communities (Rizvi et al 1992;Scrivanti et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Allelochemicals aff ect various metabolic processes in organisms, including changes in membrane permeability, ion absorption (Gniazdowska & Bogatek 2005) and inhibition of electron transport in respiration and photosynthesis (Abrahim et al 2000), as well as changes in enzyme activities (Singh et al 2009) and inhibition of cell division Acta bot. bras.…”
Section: Introductionmentioning
confidence: 99%